The Effectiveness of Using the Modified Early Warning Score (MEWS) in Early Detection of Patient Deterioration in the ICU - Angriawan Angriawan; Reghula Maryeti Sandra (International Journal of Health Sciences, 2025)
Background: Patients in Intensive Care The intensive care unit (ICU) is at high risk for sudden deterioration. Early detection of changes in clinical status is crucial for improving patient outcomes. Modified Early Warning Score (MEWS) is a simple scoring system based on vital signs that is used to predict the likelihood of patient deterioration. Objective: This study aims to evaluate the effectiveness of using the MEWS score in early detection of worsening patient conditions in the ICU. Methods: The study used an observational quantitative design with a prospective cohort approach. The study sample was 60 ICU patients at Hospital “X” who were assessed using the MEWS score during 7 days of treatment. The observed variables were the MEWS score and the incidence of deterioration (increased need for mechanical ventilation, higher ICU transfer, or death). Analysis was performed using sensitivity, specificity, and logistic regression tests. Results: A MEWS score ≥5 had a sensitivity of 85% and a specificity of 78% in detecting patient deterioration. Regression analysis showed that the MEWS score significantly predicted the incidence of deterioration (p < 0.01). Conclusion: The MEWS score has been shown to be effective as an early detection tool for patient deterioration in the ICU. Routine use of this score can help nurses and physicians intervene more quickly.